Hubungan antara Perilaku Prososial dengan Psychological Well-Being pada Remaja - Megawati, Elisa; Herdiyanto, Yohanes Kartika (Jurnal Psikologi Udayana, 2016)
Psychological well-being is a life that goes well, and is a combination of feeling good and functioning themselves effectively (Huppert, 2009). Humans in every age group would want to achieve psychological well-being during their lifetime, as well as adolescencts. Adolescencts can achieve psychological well-being when they are actively develop positive behaviors during adolescence. One of the positive behavior that should be developed during adolescence is prosocial behavior. Prosocial behavior involve altruism, so that adolescencts who can show helping behavior and give positive consequences for others, are expected to help adolescencts feel good about themself. This study aimed to determine the correlational between prosocial behavior with psychological well-being in adolescent in the city of Denpasar.The sampling technique used in this study is cluster random sampling. Subjects of this research are 214 adolescents from age 15-17 years old (m=91, f=123). Researcher deploy two scales, the psychological well-being scale modified from the Scales of Psychological Well-Being (Ryff, 1995) consisted of 30 item with a reliability coefficient of 0,898 and prosocial behavior scale consisted of 68 item with a reliability coefficient of 0,958. The data obtained in this study were analyzed by simple regression analysis to examine correlational between prosocial behavior and psychological well-being.Regression analysis results t value 11,203 and P = 0,000 ( P < 0,05). It means prosocial behavior and psychological well-being are significantly and positively correlated, when prosocial behavior is high they will have a high score on psychological well-being too. Coefficient of determination equal to 0,372 indicates prosocial behavior contribution to psychological well-being is 37,2%, and 62,8% was contributed by other factors such as age, socioeconomic level, social relations and personality factors.Keywords: prosocial behavior, psychological well-being, adolescence.